A Socio-Pragmatic Study of a Sincere Invitation in Yemeni Spoken Arabic - Al-Hamzi, Ali Mohammed Saleh; Wiratno, Tri; Anis, Muhammad Yunus; Jamal, Mujtaba; Cahyaning, Angga (PAROLE: Journal of Linguistics and Education, 2023)
A sincere invitation is a speech act with a significant role in interpersonal communication, and the purpose of this study is to explore the speech acts commonly used by Yemeni speakers to convey sincere invitations in their daily interactions. The qualitative research approach focuses on the linguistic and social contexts in which sincere invitations are made. Data is collected through personal observation and online interviews, which simulate brief, everyday social conversations. The study includes a purposive sample of native Arabic-speaking Yemeni individuals residing in the provinces of north Yemen. The data analysis is based on Searle's speech act theory, which is used to evaluate a speaker's adherence to Felicity Requirements as an indicator of the authenticity of their invitations. The findings indicate that Yemeni speakers use declarative and interrogative sentences to convey indirect illocutionary acts of genuine invitations. Furthermore, the genuineness of these invitations is established through the observance of felicity conditions proposed by Searle.